The Influence of Motivation and Work Discipline on Employee Performance - Abid, Muhamad; Savikri, Hureyda (Golden Ratio of Data in Summary, 2025)
This research analyzes work motivation and discipline's influence on team member performance at PT. Moderland, South Tangerang. The study uses a quantitative research method with a saturated sampling technique, involving 50 employees as respondents. Data were collected through questionnaires, observation, and interviews, then analyzed using multiple linear regression analysis. The results indicate that work motivation and discipline significantly positively affect team member performance, both partially and simultaneously. Employees with higher motivation and discipline levels tend to demonstrate better work outcomes in quality, quantity, timeliness, and cooperation. The coefficient of determination also shows that these two independent variables can explain much of team member performance. This research concludes that enhancing motivation and maintaining discipline are crucial strategies for improving team member productivity and organizational effectiveness. The findings are expected to support better human resource management practices at PT. Moderland.